The deployment of social media by journalists in news discourse during public health and environmental crises in Spain (2019-2022) - Tulloch, Christopher D.; Cuartielles, Roger; Ramírez-Santos, Fernanda (Estudios sobre el Mensaje Periodístico, 2023)
The consolidation of social media as both a news source and information channel in professional news practice is a growing field within crisis communication research. This article enters the newsroom to interview those journalists charged with the coverage and information management of high-profile public emergencies as to how they employ social media in their news production routines. Results reveal an across-the-board consensus on the positive consequences of this trend such as user interaction or source availability, the signalling of more negative aspects such as acceleration, intoxication or the proliferation of unfiltered “news” and the existence of professional issues which are yet to be addressed such as the maintenance of certain boundaries regarding information access between journalists and citizens in crisis communication scenarios.